2011
DOI: 10.1016/j.cpc.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Octree-based, GPU implementation of a continuous cellular automaton for the simulation of complex, evolving surfaces

Abstract: Presently, dynamic surface-based models are required to contain increasingly larger numbers of points and to propagate them over longer time periods. For large numbers of surface points, the octree data structure can be used as a balance between low memory occupation and relatively rapid access to the stored data. For evolution rules that depend on neighborhood states, extended simulation periods can be obtained by using simplified atomistic propagation models, such as the Cellular Automata (CA). This method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The optimised use of further GPGPU data structures are used to minimise the amount of traffic between the CPU and GPGPU, which is known to be a bottleneck. However, Ferrando et al [24] are more keenly interested in carrying out the high resolution of simulation in feasible amounts of time, and so do not directly claim that this approach provides speed ups because their system works as a co-operation of the CPU and GPGPU. In experiments conducted later in this paper it is found that with the GPGPU as a co-processor, a certain amount of instruction passing from the CPU is necessary.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimised use of further GPGPU data structures are used to minimise the amount of traffic between the CPU and GPGPU, which is known to be a bottleneck. However, Ferrando et al [24] are more keenly interested in carrying out the high resolution of simulation in feasible amounts of time, and so do not directly claim that this approach provides speed ups because their system works as a co-operation of the CPU and GPGPU. In experiments conducted later in this paper it is found that with the GPGPU as a co-processor, a certain amount of instruction passing from the CPU is necessary.…”
Section: Related Workmentioning
confidence: 99%
“…There are circumstances where a sparse implementation has been implemented on a GPGPU, for example Ferrando et al (2011) [24] have employed an Oct-tree representation which subdivides a 3 dimensional cube of space into 8 smaller cubes at each branch of the tree. Although this does mean that the tree structure must be stored and manipulated using the CPU, a lot of processing can still be carried out on the GPGPU.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal surfaces of any orientation can be created by replicating the orthorhombic unit cell along the three axes. The use of the unit cell in combination with an octree data structure enables a significant reduction in memory use and a dramatic increase in the simulation speed for these models [19].…”
Section: Triclinic Unit Cellmentioning
confidence: 99%
“…To make this large number of simulations feasible, an efficient CCA simulator is needed. We use a fast, GPU-based implementation [19], whereby each hemisphere simulation takes about 3 seconds. The initial hemisphere surface contains 472298 surface atoms and ∼ 1.4 · 10 6 atoms are removed per simulation.…”
Section: Objective Functionmentioning
confidence: 99%